Transaksi Jual Beli Chip Dalam Game Online Indoplay Menurut Fiqh Muamalah - Haryanto, Endang; Juniarti, Amelia; Nurjanah Putri, Ezi; Fransisca, Sherly; Anggraini, Yola (MENYALA: Jurnal Pengabdian Masyarakat, 2024)
This research aims to find out the transaction process tool buy chips in the Indoplay online game which took place in Padang Pelasan Village, Seluma Regency, then carry out an Islamic legal analysis of chip buying and selling transactions in the Indoplay online game according to muamalah fiqh. This research uses a qualitative type with a phenomenological approach. Data collection techniques include; observation, interviews and documentation, techniques used in data collection include: observation, interviews and documentation, in data analysis using interactive models (Miles and Huberman, where the analysis process is carried out simultaneously with the observation and interview process and documentation is directly analyzed. Results Research shows that; the process of implementing chip buying and selling transactions in Indoplay online games in Padang Pelasan Village, Seluma Regency begins with friends conveying this buying and selling occurs in two ways, namely offline between playing friends and "hanging out" friends, as well as online via a Facebook group which displays the nominal value of the chips being sold and also the nominal selling price, after which the buyer asks for the location of the place to make the transaction or it could also be said COD (Cash on Delivery). After the seller and buyer meet at the predetermined place and time , then that is where the transaction between the seller and the buyer takes place, the seller sends chips to the buyer's Indoplay account and the buyer gives money according to the nominal amount of money that was previously agreed upon.